East Asian development model 21st century perspectives - Hua, Shiping 1956-; Hu, Ruihua (Routledge contemporary Asia series, 2015)
Given the impressive growth in East Asia after World War II, initially led by Japan, the region's development models have been scrutinized since the 1980s. The shared Confucian cultural heritage, strong government guidance, and export led economies were often cited as contributors to the impressive growth. However, major changes have taken place in Asia on and around the turn of the century: Japan experienced two decades of economic slow-down, while China has become the second largest economy in the world. Bearing this in mind, is it even possible to formulate an East Asian development model in the context of a shifting 21st century? And if so, what is it? This book addresses this issue by looking at the economic, political and cultural perspectives of China, Japan and South Korea, focusing on dynamism and potential consensus regarding an East Asian development model. The chapters offer a historical background to the East Asian development model, as well as in-depth case studies of each of the countries concerned to show that whilst the East Asian development does have distinct characteristics as compared with other areas, and other countries may draw some insights from the East Asian experience, it is not a panacea that fits all circumstances and fits all times"